Strategi Sukses K-Pop Memasuki Pasar Musik Mainstream: Bighit Entertainment, BTS, dan ‘Army’ - Ni Made Santika Krisna Diari; Luh Putu Mahyuni (Universitas Pendidikan Nasional, 2019)
ABSTRACTThe purpose of this study is to identify the differentiation strategy of K-pop agency in the digital economic era, as well as the role of fans in their application. The focus of this research is on BigHit Entertainment the agency that manages the current phenomenal K-pop group, namely BTS; as well as the behavior of their fans. This descriptive qualitative research uses secondary data collected from articles and videos related to the agency, the group, and their fans; as well as observational data from social media, like Twitter. This research use Miles and Huberman model of analisys techniques which include data reduction, data presentation, and conclusion drawing. The results of analysis show that BigHit Entertainment applied the strategies of product differentiation, marketing channel differentiation and image differentiation in order to obtain competitive advantage. Those differentiation strategies is in line with the tactical steps of digital marketing that begin with an understanding of consumer behavior, and then continued with human-oriented marketing for brand attractiveness, content marketing for brand recognition, omnichannel marketing for brand commitment, and engagement marketing for brand affinity. During the process of strategy implementation, fans that mostly consist of young people and women played a major role as a good brand advocate and contents distributors.